Factors Influencing Purchasing Decisions in Social Commerce: Brand Image and Brand Trust as Mediating Variables - Alfi Aziza; Imelda Hawrencia; Vio Sanya Farrasyanti; Adilla Anggraeni (Cita Konsultindo Research Center, 2024)
This study examines the factors that influence consumer purchase decisions on the TikTok social commerce platform, focusing on the influence of brand ambassadors, brand image, and sales promotion. Using data from 294 respondents who engaged in e-commerce through TikTok Shop, this study explores the mediating role of brand image and brand trust in the relationship between brand ambassador characteristics and purchase decisions, as well as the impact of review quantity and quality on purchase decisions and brand trust. The results show that brand ambassador characteristics and brand image have a significant influence on purchase decisions, while sales promotion does not have a significant effect. High quality reviews proved to be important in building brand trust, which indirectly influence purchase decisions. The findings highlight the importance of marketing strategies involving credible endorsers and trustworthy online reviews to influence consumer behaviour on social commerce platforms.